Teachers and Teaching - Shahaf Gal (Journal of Research in Rural Education, 1993)
In this section I explore two domainsI believe to be importantfor theoretical and applied network research for rural education. First, the study of networks for teaching must establish the conditions and features of educational practice in which the networks get used. Focusing on rural education offers an opportunity to create a research agenda around a specific group of teachers who teach in a particular educational setting. The second domain is the knowledge of the kinds of network use, within the set conditions and in relation to the issues considered important by users. Once the important factors for rural teachers have been established, researchers have to determine whether or not networks support rural education, or whether new educational issues emerge as a result of network use. The five preceding cases are used to demonstrate the construction ofsuch a research design, and to establish an agenda for future research.